Pertanggungjawaban Pidana Bagi Pelaku Tindak Pidana Pencurian Pengidap Gangguan Skizofrenia Criminal Liability For People Of The Crime Of Theft For People With Schizophrenia Disorder - Hasan, Puan Maharani; Maulani, Diah Gustiniati; Tamza, Fristia Berdian; Firganefi, Firganefi; Husin, Budi Rizki (Innovative: Journal Of Social Science Research, 2025)
Criminal actions are perpetrated not only by ordinary individuals but also by those with mental problems, as indicated in judgment number: 442/Pid.B/2021 / PNKot). The ruling pertains to individuals with mental problems who commit theft, as outlined in Article 363, paragraph 2. Moreover, there exists proof of a Visum Et Repertum indicating that the prisoner suffers from schizophrenia; still, the court opts for incarceration. The primary issue in this research is the judge's consideration in adjudicating cases involving perpetrators of theft with mental problems, specifically on sentencing and the assessment of criminal culpability for these individuals.This strategy employs normative and empirical legal methods to address the issue. The used data comprises primary, secondary, and tertiary data. The participants in this research were Judges from the District Court of Kota Agung, representatives from the Pringsewu State Prosecutor's Office, a psychiatric expert at the Lampung Provincial Psychiatric Hospital, and a lecturer in the criminal law division at the Faculty of Law, University of Lampung. During the processing of data acquired by data identification. Data classification and data preparation. Qualitative analysis for data examination.